Conductive nylon composite material and preparation process thereof
By pretreating and modifying the filler, and using high-pressure liquid phase homogenization treatment and freeze-drying to form a complex microstructure, the problems of uneven distribution of fillers and weak interface bonding force in conductive nylon materials are solved, and the conductive and mechanical properties are improved.
Patent Information
- Application Number
- CN202510076000.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing conductive nylon materials have shortcomings in terms of electrical conductivity and mechanical properties. The uneven distribution of fillers leads to a decrease in conductivity, and the interface bonding force is weak, making it easy to delaminate or peel, affecting the overall performance of the material.
By pretreating and modifying the filler, graphene and MXene materials are expanded using supercritical solvents, and complex microstructures are formed by high-pressure liquid phase homogenization treatment and freeze-drying, promoting uniform distribution of the filler and the formation of conductive networks.
The uniform distribution of fillers and the formation of conductive networks are achieved, the connectivity and efficiency of conductive paths are improved, and the overall mechanical properties and stability of the conductive properties of the material are enhanced.
Smart Images

Figure CN119842220A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer composite materials, and in particular to a conductive nylon composite material and a preparation process thereof. Background Art
[0002] Conductive nylon is a functional composite material that gives traditional nylon (such as PA6 and PA66) conductive properties by introducing conductive fillers. Nylon itself has excellent mechanical strength, chemical corrosion resistance and good processing properties, but its inherent insulation properties limit its use in certain high-demand application scenarios. By adding conductive fillers, conductive nylon not only retains these advantages, but also obtains significant conductive properties, making it show broad application prospects in the fields of electromagnetic shielding, static dissipation, antistatic coatings, smart sensors and flexible electronic devices.
[0003] Existing conductive nylon materials still have deficiencies in terms of conductive properties and mechanical properties. Since it is difficult to achieve uniform dispersion of fillers in traditional preparation processes, conductive fillers are prone to agglomeration, resulting in uneven distribution of fillers in the matrix, which reduces conductive efficiency and may also form local stress concentration points, affecting the overall mechanical properties of the material; secondly, the interface bonding force between the filler and the polymer matrix is weak, and stratification or peeling is prone to occur, which weakens the stability and durability of conductive properties and leads to a decrease in the overall performance of the conductive nylon material. Therefore, the present invention provides a conductive nylon composite material and a preparation process thereof to solve the above problems. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention aims to provide a conductive nylon composite material and a preparation process thereof.
[0005] A preparation process of a conductive nylon composite material comprises the following steps:
[0006] (1) Pretreatment and modification of fillers: Graphite and MXene materials are placed in a supercritical solvent and expanded for 2-4 hours at a temperature of 350-400°C and a pressure of 25-35 MPa. During the treatment process, a silane coupling agent is introduced by spraying to form a suspension containing expanded graphene.
[0007] The carbon nanotubes and silver nanowires are added to a dispersion medium, initially dispersed by ultrasonic treatment, and a silane coupling agent is added for surface modification to form a dispersion;
[0008] (2) Mixing and high-pressure liquid homogenization: The suspension and the dispersion are mixed evenly, and the mixed solution is treated at a pressure of 180-220 bar using a high-pressure liquid homogenizer;
[0009] (3) Freeze drying and pore structure formation: The treated mixed solution is poured into a mold and rapidly cooled to below -80°C to form ice crystals in the solution. The ice crystals and solvent are then removed by low-temperature vacuum drying, leaving a uniformly distributed pore structure to form a composite filler powder.
[0010] (4) Melt blending and molding: melt blending nylon 6 and polycarbonate in a twin-screw extruder, setting the temperature to 230-270°C and the rotation speed to 250-350rpm, adding composite filler powder after sufficient preheating and complete melting, and mixing and dispersing uniformly; after melt blending, injection molding or extrusion molding and cooling to room temperature to obtain a conductive nylon composite material;
[0011] The conductive nylon composite material comprises the following raw materials in parts by weight: 40-60 parts of nylon 6, 30-50 parts of polycarbonate, 5-15 parts of expanded graphene, 3-10 parts of MXene material, 5-10 parts of carbon nanotubes, 2-8 parts of silver nanowires, and 0.1-1 part of a silane coupling agent.
[0012] Furthermore, the MXene material is a two-dimensional transition metal carbide or nitride obtained from MAX phase ceramics by chemical etching and mechanical exfoliation, and the MAX phase ceramics are Ti3C2T x .
[0013] Furthermore, the supercritical solvent is supercritical carbon dioxide.
[0014] Furthermore, the dispersion medium is water or ethanol.
[0015] Furthermore, the silane coupling agent is KH550.
[0016] Furthermore, in the pretreatment and modification of the filler (1), for graphite and MXene materials, the amount of silane coupling agent used is 0.1-0.5% of the total weight of the graphite and MXene materials; for carbon nanotubes and silver nanowires, the amount of silane coupling agent used is 0.1-0.7% of the total weight of the carbon nanotubes and silver nanowires.
[0017] Furthermore, the mixed solution is treated with a high-pressure liquid homogenizer for 3-5 cycles.
[0018] Furthermore, the low-temperature vacuum condition is a temperature of -50 to -90°C and a vacuum degree of 1-10Pa.
[0019] Furthermore, the raw materials in parts by weight also include 1-3 parts of maleic anhydride grafted ethylene-octene copolymer.
[0020] A conductive nylon composite material is prepared by the preparation process of the conductive nylon composite material.
[0021] The beneficial effects achieved by the present invention are as follows: 1. The present invention constructs a complex microstructure through the ice crystal template method and freeze drying, which promotes the uniform distribution of fillers and the formation of a conductive network. During the freezing process, water molecules form ice crystals as physical templates, which are removed during the freeze drying process, leaving evenly distributed pores, providing more accommodation space for fillers, and guiding the fillers to self-assemble into a specific three-dimensional network, thereby improving the connectivity and efficiency of the conductive path. Among them, the graphene sheets form a continuous conductive plane on the pore wall, the carbon nanotubes form a vertical conductive channel in the pore, and the silver nanowires are filled into the pores to further enhance the conductive performance; in addition, the pore structure formed by the ice crystal template increases the contact area between the filler and the nylon substrate, so that the silane coupling agent can better play its interfacial bonding role, enhance the chemical bonding between the filler and the substrate, and improve the overall mechanical properties of the material by dispersing stress.
[0022] 2. The present invention forms a multi-scale conductive network by complementing each other with fillers of different sizes and shapes, thereby improving the conductive path and enhancing the overall conductive efficiency. The two-dimensional sheet materials (graphene and MXene materials) form a large-area conductive plane in the matrix, providing a good conductive foundation; one-dimensional carbon nanotubes are interspersed between the two-dimensional sheets to form a vertical conductive channel, enhancing the overall conductivity; zero-dimensional silver nanowires fill the high-resistance area to ensure the continuity and efficiency of the conductive network. This multi-scale structure can maintain stable conductive performance under complex stress conditions, reduce local stress concentration, and improve the impact resistance of the material.
[0023] 3. The present invention combines silane coupling agent modification with expansion treatment to enhance the interfacial bonding force between the filler and the polymer matrix material. The silane coupling agent can form a stable chemical bond on the surface of the filler, improve wettability, make it easier to be wrapped by the polymer matrix material, and reduce interface voids and defects. The expansion treatment expands the interlayer spacing of graphene and MXene materials through supercritical solvents, which is convenient for the insertion of other fillers to form an intercalated structure. The silane coupling agent is introduced during the expansion process and adheres to the expanded sheet to form a stable suspension, which further enhances the interfacial bonding force and promotes the uniform dispersion of the filler in the matrix.
[0024] 4. The present invention utilizes the synergistic enhancement effect. The pore structure formed by ice crystals and freeze-drying increases the contact area between the filler and the nylon substrate, so that the silane coupling agent can better play the role of interfacial bonding and enhance chemical bonding. The ice crystal template method helps to evenly distribute the filler, especially in the graphene and MXene sheets after expansion treatment, to improve the dispersibility and stability. Under the joint action, the filler is not only evenly dispersed in the matrix, but also forms a complex conductive network on the microstructure, thereby improving the conductivity and impact resistance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The schematic flow chart of the preparation process of the conductive nylon composite material used in the present invention. DETAILED DESCRIPTION
[0026] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments.
[0027] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0028] Example 1: A process for preparing a conductive nylon composite material, such as Figure 1 As shown, the following steps are included:
[0029] (1) Pretreatment and modification of fillers: Graphite and MXene materials were placed in a supercritical carbon dioxide solvent and expanded at a temperature of 370°C and a pressure of 30 MPa for 3 hours. During the treatment process, a silane coupling agent of 0.3% by weight of the total weight of graphite and MXene was introduced by spraying to form a suspension containing expanded graphene;
[0030] The carbon nanotubes and silver nanowires are added to deionized water, preliminarily dispersed by ultrasonic treatment, and 0.5% of the total weight of the carbon nanotubes and silver nanowires by silane coupling agent is added for surface modification to form a dispersion;
[0031] (2) Mixing and high-pressure liquid homogenization: The suspension and the dispersion were mixed evenly, and the mixed solution was treated with a high-pressure liquid homogenizer at a pressure of 200 bar, with a cycle number of 4 times;
[0032] (3) Freeze drying and pore structure formation: the treated mixed solution is poured into a mold, rapidly cooled to below -80°C, and then low-temperature vacuum dried at -70°C and a vacuum degree of 5 Pa to remove ice crystals and solvents to form a composite filler powder;
[0033] (4) Melt blending and molding: Nylon 6 and polycarbonate were melt blended in a twin-screw extruder at a set temperature of 250°C and a rotation speed of 300 rpm. After being fully preheated and completely melted, the composite filler powder was added and mixed and dispersed evenly. After melt blending, the conductive nylon composite material was obtained by injection molding and cooled to room temperature.
[0034] The weight proportions of the raw materials are: 50 parts of nylon 6, 40 parts of polycarbonate, 10 parts of expanded graphene, 7 parts of MXene material, 8 parts of carbon nanotubes, 5 parts of silver nanowires, and 0.12 parts of silane coupling agent.
[0035] Example 2: A process for preparing a conductive nylon composite material, such as Figure 1As shown, the following steps are included:
[0036] (1) Pretreatment and modification of fillers: Graphite and MXene materials were placed in a supercritical carbon dioxide solvent and expanded at a temperature of 360°C and a pressure of 28 MPa for 3.5 hours. A silane coupling agent of 0.4% by weight of the total weight of graphite and MXene was introduced by spraying to form a suspension containing expanded graphene.
[0037] The carbon nanotubes and silver nanowires are added to anhydrous ethanol, preliminarily dispersed by ultrasonic treatment, and 0.6% of the total weight of the carbon nanotubes and silver nanowires by silane coupling agent is added for surface modification to form a dispersion;
[0038] (2) Mixing and high-pressure liquid homogenization: The suspension and the dispersion were mixed evenly, and the mixed solution was treated with a high-pressure liquid homogenizer at a pressure of 210 bar for 3 cycles;
[0039] (3) Freeze drying and pore structure formation: the treated mixed solution is poured into a mold, rapidly cooled to below -80°C, and then low-temperature vacuum dried at -60°C and a vacuum degree of 8Pa to remove ice crystals and solvents to form a composite filler powder;
[0040] (4) Melt blending and molding: Nylon 6, polycarbonate and maleic anhydride grafted ethylene-octene copolymer were melt blended in a twin-screw extruder at a set temperature of 240°C and a rotation speed of 320 rpm. After being fully preheated and completely melted, the composite filler powder was added and mixed and dispersed evenly. After melt blending, the conductive nylon composite material was obtained by injection molding and cooled to room temperature.
[0041] The weight proportions of each raw material are: 45 parts of nylon 6, 35 parts of polycarbonate, 12 parts of expanded graphene, 5 parts of MXene material, 7 parts of carbon nanotubes, 4 parts of silver nanowires, 0.14 parts of silane coupling agent (KH550), and 1.5 parts of maleic anhydride grafted ethylene-octene copolymer.
[0042] Example 3: A process for preparing a conductive nylon composite material, such as Figure 1 As shown, the following steps are included:
[0043] (1) Pretreatment and modification of fillers: Graphite and MXene materials were placed in a supercritical carbon dioxide solvent and expanded at a temperature of 380°C and a pressure of 32 MPa for 2.5 hours. During the treatment process, a silane coupling agent of 0.5% by weight of the total weight of graphite and MXene was introduced by spraying to form a suspension containing expanded graphene;
[0044] The carbon nanotubes and silver nanowires are added to deionized water, preliminarily dispersed by ultrasonic treatment, and 0.7% of the total weight of the carbon nanotubes and silver nanowires by silane coupling agent is added for surface modification to form a dispersion;
[0045] (2) Mixing and high-pressure liquid homogenization: The suspension and the dispersion were mixed evenly, and the mixed solution was treated with a high-pressure liquid homogenizer at a pressure of 190 bar, with a cycle number of 4 times;
[0046] (3) Freeze drying and pore structure formation: the treated mixed solution is poured into a mold, rapidly cooled to below -80°C, and then low-temperature vacuum dried at -80°C and a vacuum degree of 10 Pa to remove ice crystals and solvents to form a composite filler powder;
[0047] (4) Melt blending and molding: Nylon 6 and polycarbonate were melt blended in a twin-screw extruder at a set temperature of 260°C and a rotation speed of 280 rpm. After being fully preheated and completely melted, the composite filler powder was added and mixed and dispersed evenly. After melt blending, the conductive nylon composite material was obtained by injection molding and cooled to room temperature.
[0048] The weight proportions of the raw materials are: 55 parts of nylon 6, 45 parts of polycarbonate, 8 parts of expanded graphene, 9 parts of MXene material, 6 parts of carbon nanotubes, 6 parts of silver nanowires, and 0.17 parts of silane coupling agent.
[0049] Comparative Example 1: Referring to Example 1, only graphene is used as the conductive filler, and the surface is modified by a silane coupling agent. The specific process is as follows:
[0050] (1) Pretreatment and modification of filler: adding 0.3% of the weight of silane coupling agent to graphene and mixing evenly to form a suspension;
[0051] (2) Mixing and high-pressure liquid homogenization: The suspension was treated with a high-pressure liquid homogenizer at a pressure of 200 bar, with a cycle number of 4 times;
[0052] (3) Freeze drying and pore structure formation: the treated solution is poured into a mold, rapidly cooled to below -80 °C, and then low-temperature vacuum dried at -70 °C and a vacuum degree of 5 Pa to remove ice crystals and solvents to form a composite filler powder;
[0053] (4) Melt blending and molding: Nylon 6 and polycarbonate were melt blended in a twin-screw extruder at a set temperature of 250°C and a rotation speed of 300 rpm. After being fully preheated and completely melted, the composite filler powder was added and mixed and dispersed evenly. After melt blending, the conductive nylon composite material was obtained by injection molding and cooled to room temperature.
[0054] The weight proportions of the raw materials are: 50 parts of nylon 6, 40 parts of polycarbonate, and 30 parts of graphene.
[0055] Comparative Example 2: Referring to Example 1, the ice crystals are not formed by rapid cooling to below -80°C. The specific process is as follows:
[0056] (1) Same as Example 1;
[0057] (2) Same as Example 1;
[0058] (3) Freeze drying and pore structure formation: The treated mixed solution is subjected to low-temperature vacuum drying at -70°C and a vacuum degree of 5 Pa to remove the solvent and form a composite filler powder;
[0059] (4) The conductive nylon composite material is obtained in the same manner as in Example 1. The weight proportions of the raw materials are the same as in Example 1.
[0060] Performance test: The conductive nylon composite materials of Examples 1-3 and Comparative Examples 1-2 were prepared into standard specimens using a Haitian Plastics SA600 injection molding machine, and relevant performance tests were performed;
[0061] 1. Izod notch impact strength test: At room temperature (25°C), the Izod notch impact strength of the sample is tested according to GB / T1043-93, with an impact energy of 1.0J and a support span of 40mm.
[0062] 2. Tensile strength and elongation at break test: At room temperature (25°C), the tensile strength and elongation at break of the sample are tested according to GB / T1040-06, the standard distance is 50mm, and the tensile speed is 50mm / min±10%.
[0063] 3. Bending strength and bending modulus test: At room temperature (25°C), according to GB / T9341-2008, the bending strength and bending modulus of the sample are tested. The test speed is 2mm / min, the sample length is 80mm, and the support distance is 64mm.
[0064] 4. Surface resistance test: At room temperature (25°C) and relative humidity of 50%±10%, use a surface resistance meter to test resistance according to GB / T 1410-2006, with a test voltage of 500V, a stabilization time of 60 seconds, and a probe spacing of 100mm.
[0065] The above related performance test results are shown in Table 1.
[0066] Table 1 Test results of relevant properties of conductive nylon composite material specimens
[0067]
[0068] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A process for preparing a conductive nylon composite material, characterized in that: The following steps are involved: (1) Pretreatment and modification of fillers: Graphite and MXene materials are placed in a supercritical solvent and expanded for 2-4 hours at a temperature of 350-400°C and a pressure of 25-35 MPa. During the treatment process, a silane coupling agent is introduced by spraying to form a suspension containing expanded graphene. The carbon nanotubes and silver nanowires are added to a dispersion medium, initially dispersed by ultrasonic treatment, and a silane coupling agent is added for surface modification to form a dispersion; (2) Mixing and high-pressure liquid homogenization: The suspension and the dispersion are mixed evenly, and the mixed solution is treated at a pressure of 180-220 bar using a high-pressure liquid homogenizer; (3) Freeze drying and pore structure formation: the treated mixed solution is poured into a mold and rapidly cooled to below -80°C to form ice crystals in the solution. The ice crystals and solvent are then removed by low-temperature vacuum drying to form a composite filler powder. (4) Melt blending and molding: melt blending nylon 6 and polycarbonate in a twin-screw extruder, setting the temperature to 230-270°C and the rotation speed to 250-350rpm, adding composite filler powder after sufficient preheating and complete melting, and mixing and dispersing uniformly; after melt blending, injection molding or extrusion molding and cooling to room temperature to obtain a conductive nylon composite material; The conductive nylon composite material comprises the following raw materials in parts by weight: 40-60 parts of nylon 6, 30-50 parts of polycarbonate, 5-15 parts of expanded graphene, 3-10 parts of MXene material, 5-10 parts of carbon nanotubes, 2-8 parts of silver nanowires, and 0.1-1 part of a silane coupling agent.
2. The preparation process of a conductive nylon composite material according to claim 1, characterized in that: The MXene material is a two-dimensional transition metal carbide or nitride obtained from MAX phase ceramics by chemical etching and mechanical exfoliation. The MAX phase ceramic is Ti3C2T x .
3. The preparation process of a conductive nylon composite material according to claim 1, characterized in that: The supercritical solvent is supercritical carbon dioxide.
4. The preparation process of a conductive nylon composite material according to claim 1, characterized in that: The dispersion medium is water or ethanol.
5. The preparation process of a conductive nylon composite material according to claim 1, characterized in that: The silane coupling agent is KH550.
6. The process for preparing a conductive nylon composite material according to claim 1, characterized in that: In the (1) pretreatment and modification of the filler, for graphite and MXene materials, the amount of the silane coupling agent used is 0.1-0.5% of the total weight of the graphite and MXene materials; for carbon nanotubes and silver nanowires, the amount of the silane coupling agent used is 0.1-0.7% of the total weight of the carbon nanotubes and silver nanowires.
7. The process for preparing a conductive nylon composite material according to claim 1, characterized in that: The number of cycles of using the high-pressure liquid homogenizer to treat the mixed solution is 3-5 times.
8. The process for preparing a conductive nylon composite material according to claim 1, characterized in that: The low temperature vacuum condition is a temperature of -50 to -90°C and a vacuum degree of 1-10Pa.
9. The process for preparing a conductive nylon composite material according to claim 1, characterized in that: The raw materials in parts by weight also include 1-3 parts of maleic anhydride grafted ethylene-octene copolymer.
10. A conductive nylon composite material, characterized in that: Prepared according to the preparation process according to any one of claims 1 to 9.
Citation Information
Patent Citations
Polycarbonate / polyamide alloy and preparation method thereof
CN101845210A
Method for preparing graphene by using modifying supercritical peeling technology
CN102107869A
Graphene / polyamide composite material as well as preparation method and application thereof
CN111909372A
Method for preparing graphene titanium carbide cross-linked thin film material and application of graphene titanium carbide cross-linked thin film material in supercapacitor
CN115763087A
Cited By
Crosslinked aromatic polyamide polymer and preparation method thereof
CN121450099A